Experimental synthesis and density functional theory investigation of radiation tolerance of Zr3(Al1‐xSix)C2 MAX phases. Issue 4 (17th February 2017) - Zapata‐Solvas, Eugenio; Christopoulos, Stavros‐Richard G.; Ni, Na; Parfitt, David C.; Horlait, Denis; Fitzpatrick, Michael E.; Chroneos, Alexander; Lee, William E.
Abstract: Synthesis, characterization and density functional theory calculations have been combined to examine the formation of the Zr3 (Al1– x Six )C2 quaternary MAX phases and the intrinsic defect processes in Zr3 AlC2 and Zr3 SiC2 . The MAX phase family is extended by demonstrating that Zr3 (Al1– x Six )C2, and particularly compositions with x ≈0.1, can be formed leading here to a yield of 59 wt%. It has been found that Zr3 AlC2 ‐ and by extension Zr3 (Al1– x Six )C2 ‐ formation rates benefit from the presence of traces of Si in the reactant mix, presumably through the in situ formation of Zry Siz phase(s) acting as a nucleation substrate for the MAX phase. To investigate the radiation tolerance of Zr3 (Al1– x Six )C2, we have also considered the intrinsic defect properties of the end‐members. A ‐element Frenkel reaction for both Zr3 AlC2 (1.71 eV) and Zr3 SiC2 (1.41 eV) phases are the lowest energy defect reactions. For comparison we consider the defect processes in Ti3 AlC2 and Ti3 SiC2 phases. It is concluded that Zr3 AlC2 and Ti3 AlC2 MAX phases are more radiation tolerant than Zr3 SiC2 and Ti3 SiC2, respectively. Their applicability as cladding materials for nuclear fuel is discussed.